2006
DOI: 10.1590/s0066-782x2006001500017
|View full text |Cite
|
Sign up to set email alerts
|

Escore para avaliação do estado nutricional: seu valor na estratificação prognóstica de portadores de cardiomiopatia dilatada e insuficiência cardíaca avançada

Abstract: OBJECTIVEDevelop a method for the evaluation of patient's nutritional status through a score that expresses universal nutritional status, as well as investigate if that score would be effi cient for the prognostic stratifi cation of advanced heart failure (HF) pts. METHODSThe score was reached by the selection of evaluation methods that would quantify nutritional status: ideal body weight percentage, thickness of tricipital skinfold, percentiles for arm muscular mass circumference, albumin serum level, lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
(52 reference statements)
2
2
0
Order By: Relevance
“…Our results are in accordance with those reported by Veloso et al 18 . However, Nakasato et al 15 and Nogueira et al 16 have reported most of the participants of HF studies as overweight.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in accordance with those reported by Veloso et al 18 . However, Nakasato et al 15 and Nogueira et al 16 have reported most of the participants of HF studies as overweight.…”
Section: Discussionsupporting
confidence: 94%
“…The current study also demonstrated that a longer disease duration is associated with an increased risk of malnutrition. However, previous studies did not show any relationship between the risk of malnutrition and disease duration 28 . This study also showed that lower BMI was one of the predictors of malnutrition.…”
Section: Discussionsupporting
confidence: 50%
“…However, previous studies did not show any relationship between the risk of malnutrition and disease duration. 28 This study also showed that lower BMI was one of the predictors of malnutrition. In accordance with the present result, previous studies have shown that HF patients who are malnourished tend to have a lower BMI.…”
Section: Discussionmentioning
confidence: 56%
“…Disproportionate mobilization and deposition of muscle and adipose tissues may occur 26 , and it is noteworthy that protein degradation plays an important role in the progression of HF 6,26,27 . The use of BMI alone, which has low sensitivity for predicting severe malnutrition among cardiac patients 7 , may not confirm the adequacy of the energy intake in patients with HF.…”
Section: Tabela 4 -Prevalence Of Inadequacy Of Habitual Intake Of Micmentioning
confidence: 99%